Hadith #3385 - Sunan Abi Dawud - Hakim ibn Hizam; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by ‘Urwat al-Bariqi through a different chain of narrators. The wordings of this version are different from those of the previous one.
Grade: Sahih

Hadith #3458 - Sunan Abi Dawud - Abdullah ibn al-Harith ibn Nawfal; Hakim ibn Hizam; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
When Abu Zur’ah made a business transaction with a man, he gave him the right of option. He then would tell him: Give me the right of option (to annul the bargain). He said: I heard AbuHurayrah say: The Messenger of Allah (ﷺ) said: Two people must separate only by mutual consent.
Grade: Hasan Sahih

Hadith #3502 - Sunan Abi Dawud - Hakim ibn Hizam; Ja'far bin Iyas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة; Yusuf bin Mahk يوسف بن ماهك الفارسي (Sunan Abi Dawud)
On his father’s authority, said that his grandfather told that the Messenger of Allah (ﷺ) forbade the type of transactions in which earnest money was paid. Malik said: This means, as we think–Allah better knows-that a man buys a slave or hires an animal, and he says: I give you a dinar on condition that if I give up the transaction or hire, what I gave you is yours.
Grade: Hasan

Hadith #4488 - Sunan Abi Dawud - Hakim ibn Hizam; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Sdqh bin Khalid al-Amwy صدقة بن خالد الأموي (Sunan Abi Dawud)
A man who had drunk wine was brought before the Prophet (ﷺ) when he was in Hunayn. He threw some dust on his face. He then ordered his Companions and they beat him with their sandals and whatever they had in their hands. He then said to them: Leave him, and they left him. The Messenger of Allah (ﷺ) then died, and AbuBakr gave forty lashes for drinking wine, and then Umar in the beginning of his Caliphate inflicted forty stripes and at the end of his Caliphate he inflicted eighty stripes. Ut
Grade: Sahih